Interactional facilitators and barriers to social relationships between students who use AAC and fellow students. Issue 1 (1st January 2018) - Østvik, Jørn; Balandin, Susan; Ytterhus, Borgunn
ABSTRACT: Purpose : This paper investigates the perceptions among parents and staff of how relational aspects among students who use AAC, fellow students, and staff may affect the students' social relationships. Methods : The study included semi-structured interviews of 6 parents and 18 staff to 7 students using AAC. The interviews were audio-recorded, transcribed verbatim, and analyzed by using a constructivist grounded theory approach. Results : The analysis identified several interactional facilitators and barriers to social relationships between students using AAC and fellow students. Conclusions : The results demonstrated the importance of considering personal as well as environmental facilitators and barriers to the student using AAC's social relationships. The complexities in how these interactional facilitators and barriers interact with each other are discussed in relation to previous research. Of special importance for the development of the students' social relationships was shared experiences between students using AAC and fellow students, environmental adaption and support provided by staff and fellow students, staff's efforts in building goodwill for students using AAC, and fellow students' confidence in using AAC. As confidence in communicating was associated with reduction of the consequences of challenging communication with students using AAC, the results indicated the importance of providing communication training to fellow students.